Keefektifan Teknik Daily Behavior Report Card (DBRC) untuk Menolong Siswa Terisolir - Lia Mei Kastuti; Ribut Purwaningrum; Agus Tri Susilo (Universitas Sebelas Maret, 2022)
Abstract: This study aims to test the effectiveness of the Daily Behavior Report Card (DBRC) technique in helping vocational students who are isolated in their social environment. The method used is experimental research with a single subject design. The subjects of this study were two students, FR from the automotive class and HA from the engine class. Data collection uses valid and reliable observation instruments for isolated students. The study's results were analyzed using the split middle technique and clinical analysis. In conclusion, DBRC is effective in helping isolated students because there is a change in behavior on the subject to become more adjusted and pro-social. Researchers recommend guidance and counseling teachers to use DBRC, which aims to increase students' positive behavior.Abstrak: Penelitian ini bertujuan untuk menguji keefektifan teknik Daily Behavior Report Card (DBRC) untuk membantu siswa SMK yang terisolir dalam lingkungan pertemanannya. Metode yang digunakan penelitian eksperimen dengan desain single subject design. Subjek penelitian ini adalah dua orang siswa, FR dari kelas otomotif dan HA dari kelas mesin. Pengumpulan data menggunakan instrumen observasi yang valid dan reliabilitas untuk peserta didik terisolir. Hasil penelitian dianalisis menggunakan splite middle technique dan analisis klinis. Kesimpulannya DBRC efektif untuk membantu peserta didik terisolir karena terdapat berubahan perilaku pada subjek menjadi lebih adjustment dan pro sosial. Peneliti merekomendasikan kepada guru bimbingan dan konseling untuk menggunakan DBRC yang bertujuan untuk meningkatkan perilaku positif peserta didik.